2000
DOI: 10.1111/j.0065-1591.2000.acp29-05.x
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine XR in the treatment of anxiety

Abstract: Objective: To present the results of numerous studies that assessed the efficacy, safety and tolerability of venlafaxine extended release (XR) in treating anxiety disorders, particularly generalized anxiety disorder (GAD). Method: Efficacy was assessed with the Hamilton Rating Scale for Anxiety, Clinical Global Impressions scale, Hospital Anxiety and Depression scale and other instruments. Standard safety and tolerability assessments were used. Results: In four placebo‐controlled trials, venlafaxine XR was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
(13 reference statements)
0
6
0
1
Order By: Relevance
“…For example, at the beginning of treatment, serotonergic agents may have a delayed onset of action and may even activate anxiety symptoms at first, with less than half of all patients experiencing complete remission of symptoms and at the cost of long-term side effects such as sexual dysfunction. 7,8 On the other hand, GABAergic benzodiazepines may have a rapid onset of action and boost early efficacy of serotonergic agents (if sedation can be avoided), and then be discontinued after shortterm administration, thus serving as a bridge to long-term serotonergic treatments. 9 Benzodiazepines can also serve as emergency relief for breakthrough anxiety over the long term, and in cases where serotonergic agents are unable to relieve all symptoms, can "top up" such treatments to lead to remission of anxiety.…”
Section: Combining Independent Mechanisms To Enhance Therapeutic Resultsmentioning
confidence: 99%
“…For example, at the beginning of treatment, serotonergic agents may have a delayed onset of action and may even activate anxiety symptoms at first, with less than half of all patients experiencing complete remission of symptoms and at the cost of long-term side effects such as sexual dysfunction. 7,8 On the other hand, GABAergic benzodiazepines may have a rapid onset of action and boost early efficacy of serotonergic agents (if sedation can be avoided), and then be discontinued after shortterm administration, thus serving as a bridge to long-term serotonergic treatments. 9 Benzodiazepines can also serve as emergency relief for breakthrough anxiety over the long term, and in cases where serotonergic agents are unable to relieve all symptoms, can "top up" such treatments to lead to remission of anxiety.…”
Section: Combining Independent Mechanisms To Enhance Therapeutic Resultsmentioning
confidence: 99%
“…The XR formulation of venlafaxine was developed to allow for prolonged duration of absorption and once-daily dosing, with the potential of an improved side-effect profile. 40 The efficacy of venlafaxine XR has been investigated in five outpatient placebo-controlled studies, which showed a consistent pattern of improvement in the treatment of GAD. 41 Four of these studies demonstrated a statistically superior improvement compared with placebo.…”
Section: Serotonin and Noradrenaline Reuptake Inhibitorsmentioning
confidence: 99%
“…Da die Patienten der TB auch hier die Therapie nach Beendigung der KKG mit einer insgesamt schwächer ausgeprägten Symptomatik begannen, ist der Prozentsatz an klinisch gesunden Patienten höher (n = 22, 84,6%) als in der TA (n = 16, 51,6%) (Tab. [Hackett et al, 2000;Gelenberg et al, 2000;Davidson et al, 1999;Rickels et al, 2000]. Unter Paroxetin lag der Rückgang bei 12 Punkten [Rocca et al, 1997;Pollack et al, 2001].…”
Section: Validierung Des Therapieeffekts: Vergleich Von Ta Und Tbunclassified